The master’s metamorphosis: Remarks on the intellectual Keynes’ path - Mazzucchelli, Frederico (Brazilian Keynesian Review, 2022)
Even though the title above may be read as pretentious, it is not. Going deeper into Keynes’s intellectual trajectory would require a careful read of all thirty volumes of the collected writings of John Maynard Keynes, and it is not the aim of this paper. However, standing on giants’ shoulders makes things easier. Based on Skidelsk’s, Dostaler’s, Carter’s, and Belluzzos’ remarks on Keynes, it is possible to point out the author’s theoretical inflection points. It’s worthing to note that nothing is forever regarding interpretations of great minds. The text aims to point out the great lines of Keynes’ reasoning until the general theory’s publication in 1936. It is not about a theoretical discussion that aspires to detail Keynes’s concepts. Still, it will provide a comparative framework to build the bases of his intellectual approach. The starting point relies on the environment in which Keynes lived.